A mesenchymal‐like phenotype and expression of CD44 predict lack of apoptotic response to sorafenib in liver tumor cells. Issue 4 (4th August 2014) - Fernando, Joan; Malfettone, Andrea; Cepeda, Edgar B.; Vilarrasa‐Blasi, Roser; Bertran, Esther; Raimondi, Giulia; Fabra, Àngels; Alvarez‐Barrientos, Alberto; Fernández‐Salguero, Pedro; Fernández‐Rodríguez, Conrado M.; Giannelli, Gianluigi; Sancho, Patricia; et al.
<x xml:space="preserve">Abstract</x> The multikinase inhibitor sorafenib is the only effective drug in advanced cases of hepatocellular carcinoma (HCC). However, response differs among patients and effectiveness only implies a delay. We have recently described that sorafenib sensitizes HCC cells to apoptosis. In this work, we have explored the response to this drug of six different liver tumor cell lines to define a phenotypic signature that may predict lack of response in HCC patients. Results have indicated that liver tumor cells that show a mesenchymal‐like phenotype, resistance to the suppressor effects of transforming growth factor beta (TGF‐β) and high expression of the stem cell marker CD44 were refractory to sorafenib‐induced cell death in in vitro studies, which correlated with lack of response to sorafenib in nude mice xenograft models of human HCC. In contrast, epithelial‐like cells expressing the stem‐related proteins EpCAM or CD133 were sensitive to sorafenib‐induced apoptosis both in vitro and in vivo. A cross‐talk between the TGF‐β pathway and the acquisition of a mesenchymal‐like phenotype with up‐regulation of CD44 expression was found in the HCC cell lines. Targeted CD44 knock‐down in the mesenchymal‐like cells indicated that CD44 plays an active role in protecting HCC cells from sorafenib‐induced apoptosis. However, CD44 effect requires a TGF‐β‐induced mesenchymal background, since the only overexpression of CD44 in epithelial‐like HCC cells is not sufficient to impair sorafenib‐induced cell death. In conclusion, a mesenchymal profile and expression of CD44, linked to activation of the TGF‐β pathway, may predict lack of response to sorafenib in HCC patients.